Gendered Esports: Predicting Why Men and Women Play and Watch Esports Games. Issue 3 (27th May 2021) - Tang, Tang; Cooper, Roger; Kucek, Jake
ABSTRACT: This study represents one of the first empirical efforts to systematically examine gender differences in esports gameplay and viewing. Notable differences and similarities were found in how and why men and women consume esports. Men watched esports for fun, whereas women watched esports to escape from life's problems. Motivations and preferences explained men's, but not women's, esports gameplay while use of chat was the strongest predictor of esports gameplay for women. In addition, availability and access largely explained esports gameplay for both men and women. Sports fandom, motivations, and uses of interactive features significantly predicted esports viewing across genders.